2009
DOI: 10.1071/zo09039
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation in monotremes: riddles in a mosaic

Abstract: The three extant genera of the Monotremata have evolved, probably from a pre-Cretaceous Gondwanan origin, independently of the Theria to display a variety of ancestral and derived features. A comparison of their thermoregulation reveals a diversity of physiology that might represent both plesiomorphic and apomorphic elements within this mosaic. In the tachyglossids, the echidnas Tachyglossus and Zaglossus, body temperature is often labile, rising as a result of activity and allowed to decline during inactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Owing to the scope of the study, preference was given to HR data collected in medium-size and larger species because differences in f between terrestrial and aquatic mammals begin to be apparent at M > 5-10 kg (Mortola and Limoges, 2006). Data were excluded if they originated from animals under anaesthesia, in hibernation or torpor; in addition, Monotremes and Marsupials were excluded because of their characteristically low body temperature and metabolic rate (Dawson, 1989;Brice, 2009). In case of multiple values or ranges of values, means were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the scope of the study, preference was given to HR data collected in medium-size and larger species because differences in f between terrestrial and aquatic mammals begin to be apparent at M > 5-10 kg (Mortola and Limoges, 2006). Data were excluded if they originated from animals under anaesthesia, in hibernation or torpor; in addition, Monotremes and Marsupials were excluded because of their characteristically low body temperature and metabolic rate (Dawson, 1989;Brice, 2009). In case of multiple values or ranges of values, means were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Basoendotherms (sensu [36]) such as tenrecs (Fig. 1d) and echidnas show the highest level of variability with rest-phase T b closely following T a during most times of the year [52][53][54][55][56].…”
Section: Daily Variability In Mammalian T Bmentioning
confidence: 99%
“…"proto-endotherms", Grigg et al 2014;Lovegrove 2012b), but it has also been considered to be a derived character related to their overall low-energy lifestyle (Brice et al 2009). Short-beaked echidnas are primarily myrmecophagous; their ant/termite diet has a low energy density, poor digestibility and low-energy feeding behaviour (McNab 1984;Redford and Dorea 1984;Cooper and Withers 2004b), and a low BMR is characteristic of myrmecophagous mammals in general (Cooper and Withers 2002).…”
Section: Basal Physiologymentioning
confidence: 99%
“…Short-beaked echidnas have a low body temperature (T b ) and basal metabolic rate (BMR) at thermoneutrality, but the extent of their thermoregulatory capability over a wide range of T a , and how this reflects their evolutionary history and prototherian phylogenetic position, remains unclear (Brice 2009). Early physiological studies (de Miklouho Maclay 1883; Sutherland 1896) suggested that short-beaked echidnas are physiologically 'primitive' due to their low and variable T b , reflecting an intermediate position between the 'lower' reptiles and 'higher' mammals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation